Referral criteria for outpatient specialty palliative cancer care: an international consensus - Hui, David; Mori, Masanori; Watanabe, Sharon M; Caraceni, Augusto; Strasser, Florian; Saarto, Tiina; Cherny, Nathan; Glare, Paul; Kaasa, Stein; Bruera, Eduardo (The lancet oncology, 2016)
Although outpatient specialty palliative-care clinics improve outcomes, there is no consensus on who should be referred or the optimal timing for referral. In response to this issue, we did a Delphi study to develop consensus on a list of criteria for referral of patients with advanced cancer at secondary or tertiary care hospitals to outpatient palliative care. 60 international experts (26 from North America, 19 from Asia and Australia, and 11 from Europe) on palliative cancer care rated 39 needs-based criteria and 22 time-based criteria in three iterative rounds. Nearly all experts responded in each round. Consensus was defined by an a-priori agreement of 70% or more. Panellists reached consensus on 11 major criteria for referral: severe physical symptoms, severe emotional symptoms, request for hastened death, spiritual or existential crisis, assistance with decision making or care planning, patient request for referral, delirium, spinal cord compression, brain or leptomeningeal metastases, within 3 months of advanced cancer diagnosis for patients with median survival of 1 year or less, and progressive disease despite second-line therapy. Consensus was also reached on 36 minor criteria for specialist palliative-care referral. These criteria, if validated, could provide guidance for identification of patients suitable for outpatient specialty palliative care.